2013
DOI: 10.1159/000351407
|View full text |Cite
|
Sign up to set email alerts
|

Laparoendoscopic Single-Site Retroperitoneoscopic Adrenalectomy versus Conventional Retroperitoneoscopic Adrenalectomy: Initial Experience by the Same Laparoscopic Surgeon

Abstract: Purpose: The purpose of this study was to demonstrate our initial experience with and the feasibility of laparoendoscopic single-site retroperitoneoscopic adrenalectomy (LESS-RA). Patients and Methods: 54 patients undergoing conventional retroperitoneoscopic adrenalectomy were compared with 27 patients undergoing LESS-RA. The adrenal tumors were considered to be benign preoperatively and <6 cm. Age, sex, laterality, body mass index, surgical indications, time to resuming oral intake, tumor size, operation time… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 22 publications
0
11
0
Order By: Relevance
“…All the eighteen studies reported operative time [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26]. The meta-analysis of these studies showed longer operative time for LESSA (WMD = 13.86 min, 95% CI: 4.43 to 23.30; p = 0.004).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…All the eighteen studies reported operative time [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26]. The meta-analysis of these studies showed longer operative time for LESSA (WMD = 13.86 min, 95% CI: 4.43 to 23.30; p = 0.004).…”
Section: Resultsmentioning
confidence: 99%
“…Overall, eighteen studies including 1307 patients (LESSA 520; CLA 787) were included in this study (Figure 1). Table I shows the basic characteristics and quality assessment of the included studies [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…LESS is a revolutionary laparoscopy because of the advantage of less bleeding, less wound pain, less risk of incisional hernia, and better cosmesis [17]. At our institution, our surgeons experience single-port laparoscopic surgery technique, such as LESS adrenalectomy, herniorrhaphy, partial nephrectomy, and robotic single-port radical prostatectomy in daily practice [18][19][20]. LESS-DN has become the standard procedure for living-donor kidney transplantation since December 2017 in our institution.…”
Section: Discussionmentioning
confidence: 99%
“…In the past few years, numerous comparative studies have investigated whether LESS-A presents considerable advantages over multi-port laparoendoscopic adrenalectomy (m-LA) or can be an alternative treatment option [ [13] , [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] ]. Three meta-analyses [ [36] , [37] , [38] ] compared the surgical outcomes of LESS-A and m-LA by analyzing approximately 225 cases of LESS-A and 449 cases of m-LA [ [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] ]. However, the results of the three meta-analyses presented considerable discrepancies in terms of outcomes, including operative time, length of hospital stay, postoperative pain scores, and required analgesic doses.…”
Section: Introductionmentioning
confidence: 99%